Trajectories of changes in oxytocin and vasopressin before, during, and after mother-infant interaction: a descriptive study of mothers and infants affected by postpartum depression - Harrison, Tyler; Tao, Amy S.; Vo, Phuonglan; Kim, Soeun; Kim, Sohye (Frontiers in Psychiatry, 2026)
BackgroundPostpartum depression (PPD) is a major public health problem with significant adverse consequences for maternal mental health and infant development. Despite this, there exists surprisingly little data concerning neurobiological underpinnings of PPD. The present study examined oxytocin (OT) and vasopressin (VP), two hormones critical for mood regulation and social/maternal behavior, to provide descriptive data regarding the role of the two hormones in PPD and intergenerational risk.MethodsTwelve postpartum mothers (5 with PPD and 7 without PPD) and their infants participated in the study. Following a baseline blood and saliva sample collection, mothers and infants engaged in a 15-min semi-structured play interaction. Blood samples were collected from mothers at 5, 10, 15, and 40min following the start of the interaction, and saliva samples were collected from mothers and infants at 20min following the start of the interaction. We documented trajectories of changes in OT and VP before, during, and after the interaction, as well as associations between mothers’ and infants’ OT and VP.ResultsWe observed sample-wide increases in maternal OT at 5, 10, 15, and 20min, and decreases in maternal VP at 15min. Infant OT was increased at 20min. Mothers with PPD showed a more gradual increase in OT during the interaction compared to mothers without PPD. Following the interaction, OT decreased and reached its pre-interaction baseline level in mothers without PPD, but such return to baseline was not observed in mothers with PPD. Maternal and infant hormone levels generally showed positive associations. The positive association was more pronounced in OT than VP, and in the non-PPD than PPD group. OT and VP generally showed negative associations. Our data further illustrated potential inter-relationships among PPD, OT, and several important maternal characteristics.ConclusionOur findings illustrate trajectories of the mother’s and infant’s OT and VP before, during, and after interactions, and alterations of these trajectories in the presence of PPD. The findings add valuable data to the field’s understanding of how the OT and VP systems function in healthy postpartum mothers and infants and how they become dysregulated in the presence of PPD.